Priapism in Chronic Myeloid Leukemia: A Rare Case - Rifqi Nuriy; Ayu S. Iswandari; Dukut Sarwandi H.A (Institute of Computer Science (IOCS), 2022)
Causes of CML not clear with a important role from gen and environment factors, such as pesticide use. Priapism in CML around 5%. The report from this case is a man 40 years old with erection complaint in 4 days, patient feel a painful and weak. Patient as a farmer. In the physical check. There is anemic palpebral conjunctiva, hepatosplenomegaly, erection. In the laboratory result, Hb 4,3, Leukocyte 354.300, peripheral blood picture suggests chronic hematological malignancy myeloid series, BMP showed chronic phase CML, cavernous sinus blood gas analysis pH 7.567 pCO2 33.7 HCO3 31.0. In the first control Hb 8.7 Leukocyte 3000, BCR ABL detected. In the second control, leukocyte 22.500. Then, patient is aspirated and winter procedure for priapism management. Patient get transfuse PRC leukodeplected with the Hb target 10, Terbutaline tab 5 mg/12 hours, Allopurinol tab 300 mg/24 hours, hydroxyurea tab 1.500 mg/24-night hours. Giving Tyrosine Kinase inhibitor was delayed when controlling time because there is leukopenia so the blood should be monitor in two weeks routinely, then, in the second control, patient given nilotinib 1x150 mg and hydroxyurea was stopped. The conclusion is patient with priapism is clinical from leukocytosis in CML. Monitoring blood routinely is more important to assess the response to therapy, in addition, it is necessary to carry out a cytogenic and molecular evaluation.